2022
DOI: 10.1186/s12872-022-02485-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing reveals a rare missense variant in DTNA in an Iranian pedigree with early-onset atrial fibrillation

Abstract: Atrial fibrillation (AF) is a morbid and heritable irregular cardiac rhythm that affects about 2%–3% of the population. Patients with early-onset AF have a strong genetic association with the disease; nonetheless, the exact underlying mechanisms need clarification. We herein present our evaluation of a 2-generation Iranian pedigree with early-onset AF. Whole-exome sequencing was applied to elucidate the genetic predisposition. Direct DNA sequencing was utilized to confirm and screen the variants in the proband… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, a missense variant (c.G681C, p.E227D, rs1477078144) in the dystrobrevin alpha (DTNA) gene associated with early-onset AF affects the Rho-(RAS homolog) signaling pathway. Variants in DTNA and the sodium voltage-gated channel alpha subunit 1 (SCN1A) gene underscore the genetic complexity underlying AF [ 82 ].…”
Section: Genetic Factors and Insights Into Afmentioning
confidence: 99%
“…Furthermore, a missense variant (c.G681C, p.E227D, rs1477078144) in the dystrobrevin alpha (DTNA) gene associated with early-onset AF affects the Rho-(RAS homolog) signaling pathway. Variants in DTNA and the sodium voltage-gated channel alpha subunit 1 (SCN1A) gene underscore the genetic complexity underlying AF [ 82 ].…”
Section: Genetic Factors and Insights Into Afmentioning
confidence: 99%
“…However, aggregating investigations have convincingly substantiated that genetic determinants exert critical roles in the initiation and perpetuation of AF, especially for idiopathic/familial AF, and, to date, a great number of rare AF-causing variations in >60 genes have been causally related to AF, amidst which the overwhelming majority encode ion channel subunits, myocardial structural proteins, signaling molecules, cardiac transcription factors, and connexins [ 52 , 53 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In addition, pan-genomic association research has revealed that common variants at ~140 genetic loci are implicated with enhanced vulnerability to AF, though merely a small fraction of these recognized variants have been experimentally validated to be pathogenic for AF thus far [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-exome sequencing (WES) is a viable and powerful technique that beyond traditional candidate gene and locus-mapping methods provides an efficient approach to find the genetic cause of heterogeneous diseases [ 16 , 17 ] like DCM [ 18 ].…”
Section: Introductionmentioning
confidence: 99%